Focus+Context Display and Navigation Techniques for Enhancing Radial, Space-Filling Hierarchy Visualizations - John Stasko; Eugene Zhang (InfoVis'00: Proceedings of the IEEE Symposium on Information Visualization, 2000)
Radial, space-filling visualizations can be useful for depicting information hierarchies, but they suffer from one major problem. As the hierarchy grows in size, many items become small, peripheral slices that are difficult to distinguish. We have developed three visualization/interaction techniques that provide flexible browsing of the display. The techniques allow viewers to examine the small items in detail while providing context within the entire information hierarchy. Additionally, smooth transitions between views help users maintain orientation within the complete information space.